2015
DOI: 10.16965/ijar.2015.218
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Variation in the Branching Pattern of Right Axillary Artery: A Case Report

Abstract: Axillary artery and its branches are prone to have variations in their course. Knowledge about such variations are important for Radiologists in imaging techniques, Surgeons,Orthopedicians and Anesthetists in performing surgeries in the axilla and giving regional nerve blocks in the axilla.During dissection of a cadaver in the department of Anatomy, PSG IMS &R, Coimbatore, India. We observed a variation in the third part of right Axillary artery. From the common trunk, Subscapular artery, Anterior and Posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…A K Manicka Vasuki et al reported that third part of axillary artery gave a common trunk which further divided in to subscapular artery anterioir circumplex humeral artery posterior circumflex artery and pronda branchii artery. This study correlates with our study but only difference is they found in right axillary artery but we found in left axillary artery [10].…”
Section: Case Reportsupporting
confidence: 93%
“…A K Manicka Vasuki et al reported that third part of axillary artery gave a common trunk which further divided in to subscapular artery anterioir circumplex humeral artery posterior circumflex artery and pronda branchii artery. This study correlates with our study but only difference is they found in right axillary artery but we found in left axillary artery [10].…”
Section: Case Reportsupporting
confidence: 93%
“…Swamy et al [6] described a variant subscapular artery taking origin from second part of axillary artery and giving rise to posterior circumflex humeral and lateral thoracic artery. Vasuki et al [7] encountered variations in the third part of axillary artery on the right side. In the present case a common trunk took origin from second part of axillary artery and then gave rise to lateral thoracic artery and circumflex scapular artery on both sides.…”
Section: Case Reportmentioning
confidence: 99%